2021
DOI: 10.3746/pnf.2021.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Positive Therapeutic Role of Selected Foods and Plant on Ailments with a Trend Towards COVID-19: A Review

Abstract: Each day since December 2019, increasing numbers of cases of the novel coronavirus 2019 (COVID-19) infection are being detected as it spreads throughout all continents of the world except Antarctica. The virus is transmitted through contact with an infected environment or person, and the symptoms include fever, cough, and difficulty breathing. The healthcare systems of many countries are overwhelmed due to limited therapeutic options and the absence of an approved vaccine. Due to its poor healthcare systems, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…3 ). Alternative therapeutic strategies based on available foods and plants have been shown to alleviate similar infections ( Fasogbon et al, 2021 ). Therefore, carotenoids from natural resources or supplements may be future therapeutic strategies against these viral diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). Alternative therapeutic strategies based on available foods and plants have been shown to alleviate similar infections ( Fasogbon et al, 2021 ). Therefore, carotenoids from natural resources or supplements may be future therapeutic strategies against these viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since no active medication is yet available and limited amounts of vaccines are used worldwide, strengthening immune systems thorough diet may be central in the combat against the virus and its related symptoms. Indeed, phytochemicals and selected foods, such as garlic, ginger, basil, drumstick, and liquorice/licorice, may inhibit several viruses including SAR-CoV by directly inhibiting either viral entry or replication, and by immunomodulation ( Anand et al, 2021 ; Fasogbon et al, 2021 ). Furthermore, phytochemical-containing foods, such as cashew nuts and ginger, have been described to exhibit many health benefits for inflammatory processes and oxidative stress, which are the key factors in developing several chronic diseases such as diabetes mellitus and metabolic syndromes ( Darvish Damavandi et al, 2019 ; Morvaridzadeh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have been known as a good source of protease inhibitors. 21 However, in addition to their antiviral potential, a detailed examination of the pharmacokinetics and bioavailability of the described compounds was required to ensure protection. Recent reports have suggested that these phytocompounds could be valuable for the development of drugs useful for the prevention of coronavirus entry and replication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that these phytocompounds could be valuable for the development of drugs useful for the prevention of coronavirus entry and replication. 21 Although, the effectiveness of allicin (L-cysteine) has been evaluated in vitro, no clinical study has been conducted to evaluate this issue. In this regard, this study is the first to evaluate the effectiveness of this drug on COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Allicin's antimicrobial effect is due to the interaction between allicin and thiol groups of different enzymes that are required for microbe surveillance (Rouf et al, 2020). Supplements containing allicin have been demonstrated to prevent basic cold infections (Fasogbon et al, 2021). Allicin's mode of action is unknown; nevertheless, it is thought to penetrate through the cells (phospholipid membranes) to prevent viral replication.…”
Section: Bioactive Molecules Of Plant‐based African Dietsmentioning
confidence: 99%